Distance(s) and the volatility of international trade(s) - Arnaud Mehl; Martin Schmitz; Cédric Tille (European Central Bank (ECB), 2019)
Does distance matter for the volatility of international real and financial transactions? We show that it does, in addition to its well-established relevance for the level of trade. A simple model of trade with endogenous markups shows that demand shocks have a larger impact on trade between more distant countries. We test this implication in two steps, relying on a broad range of real and financial transactions measures, as well as several different metrics of distance (physical, linguistic, and internet). We first show that during the Great Trade Collapse of 2007-09 international transactions fell more between countries that are more distant along the various metrics, and find that the different distance measures magnify each other's respective impacts. We then focus on a longer panel analysis of trade in goods and show that trade is more volatile between more distant countries, with again a magnification pattern across metrics of distance.
Keywords: F10; F30; 330; distance; gravity; volatility; international trade; international finance; Great Trade Collapse